Pengaruh Metode Role Playing Terhadap Hasil Belajar Muatan IPS dan Keterampilan Berbicara Siswa Kelas V SD Negeri Pamulihan 01 - Rini Apriyani; Diah Sunarsih; Budi Adjar Pranoto (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the influence of the role playing method on the learning outcomes of social studies content and speaking skills in class V of SD Negeri Pamulian 01. The method used in this study is quantitative experimentation. The sampling technique used is the saturated cluster random sampling technique which makes the entire population a sample in the study. The data obtained came from learning outcome tests and observation sheets. Data for the learning outcomes test using and observation sheets are used to collect data on students' speaking skills. The material used in this study is the economic activities of the community. Data on the learning outcomes of experimental classes and control classes were obtained with a t value of 2.666 > 2.024 and a significance value of 0.011 < 0.05. Based on the provisions applicable to the hypothesis testing that the researcher has outlined, then Ha1 is accepted and Ho1 is rejected. This means that there is a significant difference in student learning outcomes between classes that use the Role Playing learning method and those that do not use the role playing learning method. Observation data of the experimental class and control class were obtained with a t value of 6.157 > 2.024 and a significance value of 0.000 < 0.05. Based on the provisions applicable to hypothesis testing that the researcher has outlined, then Ha2 is accepted and Ho2 is rejected. This means that there is a significant difference in students' speaking skills between classes that use the Role Playing learning method and those that do not use the role playing learning method.